TBLA Mastery of Mathematical Concepts through TPS (Think Pair Share) Learning Model Aided by Conversion Tool Games - Hariyanto, Hariyanto; Utaminingsih, Sri; Santoso, Santoso (Universitas Pendidikan Ganesha, 2020)
The level of understanding of mathematical concepts is still low due to the lack of application of learning models and media that can improve students' mastery of concepts. The purpose of this study was to reveal the construction pattern of mastery of mathematical concepts through the TPS learning model assisted by conversion tool games using Transcript Based Learning Analysis (TBLA). This study involved 28 students of grade 5. In this study, it was divided into 2 cycles, namely cycle 1 focused on the unit length conversion material while the cycle concentrated on the material addition and subtraction of length unit conversion. Activities in each cycle will be recorded via video or audio, then the recording will be used as a transcript of the learning dialogue then analyzed with the type of communication reson. In addition to transcript analysis in the last activity students are given a written exam through LKS (Student Work Sheet). This study obtained the results that in the first cycle the class average value reached 75.36, the second cycle the average value reached 78.93, and the graduation percentage value reached 82%. So it can be concluded that this research is related to the mastery of the concept of addition and reduction in the conversion of units of length which is successful